Production Performance, Egg Quality, and Fecal Bacterial Population of Laying Ducks Fed Ration Supplemented by Bamboo Vinegar - Rattanawut, J.; Trairabeap, D.; Karrila, S. J.; Rodjan, P.; Theapparat, Y. (Tropical Animal Science Journal, 2019)
With the ban on the use of antibiotics in poultry feed, it is required to produce alternative substances to maintain poultry health and performance. The present study was carried out to investigate the effects of dietary supplementation at various levels of bamboo vinegar (BV) on performance, egg quality, and fecal bacterial population of laying ducks. One hundred and five 50-week-old crossbred laying ducks (Khaki Campbell × Native) were randomly allocated into five treatment groups, each with seven replicates of three ducks. The experimental ducks were fed a basal diet (antibiotic-free diet) supplemented with BV at the levels of 0%, 0.2%, 0.4%, 0.6%, or 0.8% of diet until 62 weeks of age. For the overall period (from 50 to 62 weeks of age), the dietary supplementation of BV at the levels of 0.4% and 0.6% of diet increased egg production and egg mass, and improved feed efficiency of laying ducks (p<0.01). Supplementation of BV at the level of 0.8% in the diet decreased feed intake (p<0.01). Egg quality parameters were not significantly affected by supplementation of BV (p>0.05). The population of fecal Escherichia coli was significantly decreased in the experimental ducks fed diet supplemented with BV at the levels of 0.4%, 0.6%, and 0.8% compared to the control group (p<0.01), while the population of Lactobacillus spp. remained unchanged. The present results indicate that a level of 0.4% BV supplementation in laying duck diet is sufficient for reducing fecal E. coli and improves productive performance of egg laying ducks.